An evaluation of different vaccine models to protect mice from visceral leishmaniasis - Jasim Hameed Taher (Kufa Journal for Veterinary Medical Sciences, 2012)
A soluble cocktail vaccine was  prepared from sonicated promastigotes of five Iraqi Leishmania isolates with some adjuvants (BCG and Alum), was used experimentally to protect Balb/c mice against visceral leishmaniasis. Groups of  mice were immunized with a soluble cocktail of antigens given in 75 μg /0.1 ml of phosphate buffer saline with booster at different  intervals. Full protection was observed when mice were challenged one month post vaccination ; the challenged mice were rechallenged after six weeks. At the eighth week post challenge, the results exhibited complete  resistance to the rechallenge (no parasites in culture media or impression smears of liver and spleen were noticed). A long run follow-up was performed. Five of the twelve vaccinated mice developed infection, which resolved by 16 weeks. Significant cellular and humoral response (Delayed hypersensitivity, Immunoglobulin  levels, Lymphocyte subsets, Cytokine levels, Eosinophil cationic protein and Macrophages migration inhibition) to Leishmania donovani were demonstrated in all of the groups that were  subjected to 75 μg of antigens. Protein bands of crude antigens of  Leishmania  isolates by SDS - PAGE and Western blotting and the specific protein bands for leishmanial cocktail was determined to be 18 k Da. Results of vaccination with 75 μg antigens and booster doses revealed that immunization against L.donovani could be a practical method of protection from visceral leishmaniasis.